Sistem Pembayaran Upah Karyawan Pertashop di Desa Pandan Lagan di Tinjau Dari Hukum Ekonomi Syari’ah - Fitria Ningsih; Nilfatri Nilfatri; Sayida Khoiratun Nisak; Kurniawan Kurniawan; Triyana Wulandari; Haeran Haeran (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In essence, every individual who performs work should receive compensation for what has been done so that neither party suffers any loss. This is in line with a work agreement that is usually made between two or more parties. The provision of wages (ujrah) should be based on a contractual agreement, as this forms a working relationship between the worker and the employer, outlining the rights and obligations of each party.In this study, the researcher found irregularities in wage payments, such as delayed payments to employees—sometimes exceeding the agreed pay date—and a lack of punctuality in payment schedules established at the beginning of the agreement. This results in a lack of transparency between the employee and the Pertashop owner.This research aims to explain and analyze the wage payment system applied at Pertashop from the perspective of Islamic economic law, focusing on a Pertashop located in Pandan Lagan Village. The research uses a qualitative method. Data collection techniques included in-depth interviews with the business owner and employees, observation, and documentation. This study is an empirical sociological field research.The findings indicate that, in general, the wage payment system at Pertashop has met several fundamental aspects of Islamic economic law, such as the existence of a mutually agreed employment contract and clear wage nominal. However, several issues were identified, such as delayed payments, lack of transparency in financial records, and the absence of a legally binding written contract. There is no written agreement or employment contract between the business owner and the employee, resulting in a lack of legal clarity in the working relationship. The unclear status of workers' rights—such as leave, attendance, and mechanisms for wage deductions—has the potential to cause disputes.This lack of clarity may lead to injustice and contradicts the principles of the ujrah contract in Islamic law, which guarantees clarity and certainty in the payment for services rendered. Therefore, this research recommends an improvement of the wage payment system at Pertashop by fully adopting the principles of Islamic economic law, such as clarifying the employment contract in written form, ensuring timely payments, and enhancing financial transparency and accountability.